Macrofauna asssociada a MILLEPORA ALCICORNIS LINNAEUS, 1758 (CNIDARIA: HYDROZOA) em áreas sob diferentes níveis de influência do turismo subaquático na área de proteção ambiental estadual dos Recifes de Coral (RN) - Garcia, Tatiane Martins (2006)
Associated macrofauna in Millepora alcicornis Linnaeus, 1758 (Cnidaria: Hydrozoa). The genus Millepora occurs worldwide throughout tropical seas as a regular component of coral reefs. Millepores are found in depths of less than 1m to about 40m. By providing substratum for sedentary organisms and food or shelter for mobile organisms, living corals create a rich series of habitats for a large number of species. The objective of this work was to identify and quantify all the macrofauna found in Millepora alcicornis colonies of Área de Proteção Estadual dos Recifes de Coral (RN). The samples were collected manually through SCUBA diving, in depths of less than 1 to 3m. The colonies were involved in plastic bags and, after that, extracted from the substratum with the aid of hammer and chisel. Later, the samples were fixed in 4% formalin solution. In the laboratory, the colonies were analyzed to remove the epibiotic fauna and, after that, carefully broken up for the removal of the boring fauna. A total of 1,234 individuals and 95 species of not-colonials organisms and 86 colonies and 26 species of colonial organisms were registered, belonged to the taxa Cnidaria, Crustacea, Echinodermata, Mollusca, Nemertea, Polychaeta, Porifera, Sipuncula and Tunicata. The crustaceans presented the largest number of individuals and species, followed by the sea worms and mollusks. According to the coefficient of Spearman correlation, the number of individuals and species of the not-colonials organisms increase with the growth of the colony. In relation to the colonial fauna, the tunicates had greater number of colonies and the sponges, greater species number. The epifauna of the colonial and not-colonials groups were more numerous than the endofauna. Comparisons between Scleractinia and Milleporidae can be traced because of a possible functional convergence of these taxa. It is possible to assume that the associations with corals do not depend exclusively on the species hostess, as distinct species inhabit the same species of corals in different regions. Probably the substratum had more important function, where its distinct forms promote the formation of habitats.